M60. EARLY VERSUS DELAYED PRESCRIPTION OF CLOZAPINE AND THE COGNITIVE PERFORMANCE ON SCHIZOPHRENIA. (18th May 2020) - Amoretti, Silvia; Garriga, Marina; Mezquida, Gisela; Mallorqui, Andrea; Penadés, Rafael; Oliveira, Cristina; Parellada, Eduard; Bernardo, Miquel; Garcia-Rizo, Clemente
Abstract: Background: Patients with schizophrenia display a wide and characteristic array of cognitive deficits. A range of factors has been shown to influence cognition, including cognitive reserve (CR). Amongst antipsychotics only clozapine has shown positive results on cognition to date. Although it is known that delayed initiation of clozapine may be related to poor clinical psychotic response, no previous results have been tested on relation to cognitive improvements. This study aimed to analyze the improvement in cognitive performance after starting clozapine treatment according to the early versus late treatment initiation after diagnosis. Methods: 41 patients with schizophrenia were enrolled. All subjects were assessed clinically, neuropsychologically and functionally at baseline and at the 18th week of clozapine treatment. Premorbid IQ was calculated with the vocabulary subtest of the WAIS-III and it was considered a measure of CR. For study purposes, sample was divided into early or late treatment initiation of clozapine (± 3 years after diagnosis). Lineal mixed model analyses were used while confounding from different factors. Results: There were no differences between groups in terms of gender, functional, clinical and neuropsychological outcomes at baseline and follow-up. Neither clozapine dose, nor plasma concentration of nor-clozapine, have been found to be different at 18 weeks. Significant difference in age was found (p<0.001). In early initiation clozapine treatment group (n=22), improvements in working memory, attention, executive functions, and processing speed were found. Thus, CR was the only significant factor explaining these improvements in all cognitive domains, except in processing speed that was explained by time. Late onset group (n=19) improved their cognitive performance on working memory and executive functions, both explained by CR (not time or age). Discussion: There were no differences between groups at baseline, except for age. Patients who started an early treatment of clozapine improved more cognitive domains at 18-week that those who started it later. In both cases, CR is a key factor in predicting cognitive improvement. Reducing clozapine treatment delay might represent immediate prospective improvements on cognitive domains in comparison with delayed start. Time-wise cognitive monitoring and CR enhancement at early stages of the psychotic illness/treatment may be helpful in order to prevent cognitive impairment.